Preparation method and application of solid electrolyte membrane
By preparing the Li2+bTaaXbCl6-polydopamine-coated LZCFO electrolyte membrane, the problems of low ionic conductivity and poor mechanical properties in solid polymer electrolytes are solved, and the battery performance and safety are improved.
Patent Information
- Application Number
- CN202510419263.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-03
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-04-03
AI Technical Summary
The low ionic conductivity and poor mechanical properties in solid polymer electrolytes limit the performance and safety of the battery.
By mixing lithium chloride, the first halide, LiF, Li2O and ball milling to form a first mixed powder; then stirring and drying lithium chloride, the second halide, and ammonium chloride in deionized water to form an electrolyte; then adding electrolyte and polydopamine to a saturated solution of lithium chloride, controlling the viscosity and reacting with the first mixed powder to form a Li2+bTaaXbCl6-polydopamine-coated LZCFO electrolyte; finally, the electrolyte film is coated on the polyimide-based film and atomically deposition to form a metal layer to obtain a solid electrolyte film.
It improves the mechanical strength of the electrolyte, reduces side reactions, enhances the stability of halide electrolyte in the air, promotes uniform deposition of lithium ions, reduces the generation of lithium dendrites, and extends the cycle life of the battery.
Smart Images

Figure CN119920957A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of energy materials, and in particular relates to a preparation method of a solid electrolyte membrane and its application. Background Art
[0002] At present, battery development faces two major challenges: how to improve the energy density of batteries and how to improve the safety of batteries. At present, the energy density of power batteries has reached 300 Wh / kg. In order to increase the single-charge range of electric vehicles, the energy density needs to be further improved. Replacing the current graphite anode with a lithium alloy anode can greatly improve the energy density of the battery, but lithium alloys will continue to react with the currently used liquid electrolytes. Due to its non-diffusibility, the solid electrolyte system is theoretically easier to form a stable interface, thus being compatible with the lithium alloy anode. At the same time, solid electrolytes are not easy to burn, and replacing flammable carbonate organic liquid electrolytes will significantly improve the safety of the battery.
[0003] Solid electrolytes are the core components of solid-state batteries, and their ion transport capacity and mechanical stability determine the overall performance of the battery. Among various solid electrolytes, inorganic solid electrolytes have the characteristics of high ionic conductivity and high mechanical strength. However, their brittleness and complex preparation process may limit the flexibility of the battery and increase the production cost of the battery. In contrast, solid polymer electrolytes have shown great advantages in commercial applications, such as low cost, excellent flexibility and good interface contact. However, challenges such as relatively low ionic conductivity and poor mechanical properties of solid polymer electrolytes still exist. Current halide electrolytes and halides are sensitive to water and oxygen in the air, which requires operation in a glove box environment, hindering large-scale production. The lithium metal anode in lithium metal batteries in halide electrolytes is very unstable, including poor chemical stability and electrochemical stability. When using lithium metal as the anode, the current halide all-solid-state battery has poor lithium ion product uniformity, resulting in very serious lithium dendrite growth, which ultimately easily leads to serious battery life decay and short circuit. The high reactivity of halide electrolytes with the anode makes halides unable to be used as a good solid electrolyte layer. Therefore, designing solid-state electrolytes with high electrochemical and mechanical properties is crucial for advancing battery technology. Summary of the invention
[0004] The present application provides a method for preparing a solid electrolyte membrane and its application, aiming to solve the problems of low ionic conductivity and poor mechanical properties in solid polymer electrolytes to a certain extent.
[0005] In a first aspect, the present application provides a method for preparing a solid electrolyte membrane, comprising the following steps: S1, mixing lithium chloride, a first halide, LiF, and Li2O, and ball-milling to obtain a first mixed powder; S2, adding lithium chloride, a second halide, and ammonium chloride to deionized water, stirring, and drying the solution to a powder state to obtain an electrolyte, wherein the second halide is a combination of one or more of YCl3, ScCl3, ErCl3, InCl3 and TaCl4; S3, adding the electrolyte obtained in S2 to a solution saturated with lithium chloride, and then adding polydopamine, stirring, and concentrating to control the viscosity at a set value to obtain a mixed slurry; S4, mixing the first mixed powder obtained in S1 with the mixed slurry obtained in S3, and reacting them at a set pressure and a set temperature to obtain an intermediate product; S5, drying the intermediate product to obtain Li 2+b Ta a X b Cl6-polydopamine-coated LZCFO electrolyte, denoted as LTXC-PDA@LZCFO; S6, mixing the LTXC-PDA@LZCFO with a binder and a pore-forming agent, adding a solvent to prepare a slurry, dispersing and evaporating to obtain an electrolyte slurry, coating the electrolyte slurry on both sides of the polyimide-based film, and drying to obtain an electrolyte membrane; S7. Performing atomic deposition on the electrolyte membrane to form a metal layer on one side to obtain the solid electrolyte membrane.
[0006] In some embodiments, in step S1, the first halide is ZrCl4; the molar ratio of the lithium chloride, the first halide, LiF, and Li2O is d:e:f:g, wherein 0<d≤4, 0<e≤1, 0≤f≤2, 0≤g≤0.5; and the particle size of the first mixed powder after refinement is 1μm-2μm.
[0007] In some embodiments, the molar ratio of lithium chloride, the second halide, and ammonium chloride in step S2 is x:y:z, wherein 0<x≤3, 0<y≤1.5, 0<z≤3; and the drying is drying the solution to a powder state at 200-800°C. S1 obtains LZCFO (Li 2.5 ZrCl5F 0.5 O 0.5 ), S2 gets Li 2+b Ta a X b Cl6.
[0008] In some embodiments, the electrolyte in step S3 is Li 2+b Ta a X bCl6, wherein X is 0, 1 or a combination of 2 or more of Y, Sc, Er and In, 0.1≤a≤3, 0≤b≤5; the molar ratio of the electrolyte to polydopamine is 1:(0.01-0.5), the stirring is carried out at 5-200°C, and the viscosity after concentration is set to 10-5000cps.
[0009] In some embodiments, the set temperature in step S4 is -20°C to 150°C, the set pressure is 1-5 standard atmospheres, and the reaction is carried out in an atmosphere of saturated ammonia.
[0010] In some embodiments, the drying conditions in step S5 are: in a spray dryer with a nitrogen atmosphere, the drying temperature is 60-300°C.
[0011] In some embodiments, the binder in step S6 is a PMMA-based binder, the pore-forming agent is starch, the mass ratio of the electrolyte powder: binder: starch is 100: (1-5): (1-15), and the solvent is a deionized water solution containing 15% NH4Cl.
[0012] In some embodiments, the dispersion in step S6 is a dispersion of the slurry from fast to slow at a rate of 150-3000 r / min for 2h-50h; the evaporation is an evaporation at 60-120°C in a rotary evaporator to increase the solid content of the slurry to 45%~55%, and the pH is reduced to 7±1; the thickness of the polyimide-based film is 3-14μm, the porosity is ≥50%, and the coating thickness is 1μm-5μm.
[0013] In some embodiments, the metal layer in step S7 is a combination of one or more of the metal element tungsten, tungsten oxide, and tungsten carbide.
[0014] In a second aspect, the present invention further provides a use of a solid electrolyte membrane obtained by the method for preparing a solid electrolyte membrane according to any one of the first aspects in a battery.
[0015] It can be understood that the beneficial effects of the second aspect mentioned above can be found in the relevant description of the first aspect mentioned above, and will not be repeated here.
[0016] Compared with the prior art, the beneficial effects of this application are: In S1, the electrolyte is prepared by ball milling in an argon atmosphere with oxygen, aiming to form a ZrO2 and Li2O composite shell on the surface of the electrolyte particles to increase the mechanical strength of the electrolyte, while preventing the electrolyte particles from direct contact with the outside world, effectively reducing side reactions; at the same time, the stability of the halide electrolyte in the air is enhanced, and the halide electrolyte will not directly contact with the water and oxygen in the air, resulting in changes in the structure and crystal phase of the halide.
[0017] In S3, polydopamine and Li 2+b Ta a X b Cl6 halide electrolyte can form a polydopamine-halide electrolyte composite coating phase. Polydopamine and Li 2+b Ta a X b Cl6 halides have excellent stability and bonding ability, can form strong chemical bonds, and can inhibit Li 2+b Ta a X b Cl6 halide is reduced, which cannot be replaced by other substances; at the same time, polydopamine can convert Li 2+b Ta a X b The Cl6 halide electrolyte is tightly coated on the electrolyte particles obtained in S2; and polydopamine has strong negative charge, a wide conjugated area and a high π electron density, which can guide lithium ions to deposit smoothly on the negative electrode surface and reduce the generation of lithium dendrites.
[0018] In S5, spray drying technology is used for drying to obtain a better coating layer; while Li 2+b TxD b Cl6 coated LZCFO with an oxide layer can form a screw effect, that is, unstable dead lithium will react with Li 2+b TxD b Cl6 is consumed in the reaction, thereby protecting the inner layer of LZCFO to efficiently transmit lithium ions, increase the service life of the lithium metal battery and weaken the side reactions of the negative electrode.
[0019] In S6, starch is used as an additive. The glutamine amino acid in the amyloid fibers in the starch has a high adsorption energy for Li, thereby forming a stable Li-ion-rich solid electrolyte interface film on the anode during the cycle, which can homogenize the electric field and Li ion concentration, fundamentally inhibiting the formation of dendrites.
[0020] In S7, tungsten metal is deposited on the coating by an ALD atomic deposition instrument. 2+b Ta a X bAfter Cl6 reacts with dead lithium to generate XCl3, tungsten reacts with XCl3 to generate XW alloy, which prevents the side reaction products from hindering the lithium ion transmission.
[0021] In general, this solution increases the mechanical strength of the electrolyte, prevents the electrolyte particles from directly contacting the outside world, effectively reduces side reactions, and enhances the stability of the halide electrolyte in the air; improves the uniform deposition of lithium ions, and lithium ions are deposited stably on the negative electrode surface, reducing the generation of lithium dendrites. At the interface, the electric field and Li ion concentration can be homogenized, fundamentally inhibiting the formation of dendrites and increasing the battery cycle life. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0023] Figure 1 The LTC-PDA@LZCFO electrolyte obtained in step S5 of Example 1 of the present invention, wherein (a) is a schematic structural diagram; (b) is a TEM image; Figure 2 Schematic diagram of the process of obtaining the starch@LTC-PDA@LZCFO electrolyte membrane in step S6 of Example 1 of the present invention; Figure 3 The electrolyte membrane obtained in Example 1 of the present invention, wherein (a) is a schematic diagram of the structure of the electrolyte membrane; (b) is a SEM cross-sectional view of the electrolyte membrane after coating in step S6; (c) is an interface phase diagram of the electrolyte membrane after all-solid-state battery cycling; Figure 4 The EIS impedance comparison of some embodiments and comparative examples; Figure 5 This is a cycle data diagram of NCM83 / / SE / / Li battery made with the electrolyte membranes of Example 3 and Comparative Example 7. DETAILED DESCRIPTION
[0024] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0025] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0026] In this application, "at least one" means one or more, and "more than one" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, a~b (i.e. a and b), a~c, b~c, or a~b~c, where a, b, and c can be single or multiple, respectively.
[0027] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. For example, without departing from the scope of the implementation regulations of this application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.
[0028] The terms used in the embodiments of the present application are only for the purpose of describing specific implementation rules, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the implementation rules of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0029] It should be understood that in the various embodiments of the present application, the size of the serial number of each process does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the implementation regulations of this application.
[0030] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.
[0031] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0032] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.
[0033] The technical solution of the present application is illustrated below through specific embodiments and comparative examples.
[0034] In order to enable the above implementation details and operations of the present application to be clearly understood by those skilled in the art, and to significantly demonstrate the improved performance of the embodiments of the present application, the above technical solutions are illustrated by means of multiple embodiments below.
[0035] Embodiment 1: A preparation method of a solid electrolyte membrane and its application: S1: LiCl, ZrCl4, LiF and Li2O are mixed in a molar ratio of 1:1:0.5:0.5, and the materials are mixed in a mixing machine for 60 minutes, maintaining an argon atmosphere with oxygen; then the mixed materials are put into a ball mill, the ball-to-material ratio is 40:3, the ball diameter is selected to be 10mm:5mm:3mm=4:1:5, and an atmosphere mixture of oxygen and argon is introduced into the ball mill, the atmosphere mixture includes 95% volume of argon and 5% volume of oxygen, and high-energy ball milling is performed, the speed is set at 750r / min, the ball milling time is 300min, and the ball mill is opened every 30min for gas renewal, and finally the powder in the ball mill is taken out for refinement to obtain a powder with a particle size of 1μm.
[0036] S2: LiCl, TaCl4, and NH4Cl were added to deionized water at a molar ratio of 2:1:3, stirred at a stirring rate of 100 r / min for 30 min, and then the solution was dried at 200°C to a powder state.
[0037] S3: Add Li2TaCl6 to the LiCl saturated solution, and then add a certain amount of polydopamine, the molar ratio of electrolyte to polydopamine is controlled at 1:0.05, stir thoroughly at 45°C, continuously concentrate the solution, and control the viscosity to 200±20 cps.
[0038] S4: The powder obtained in S1 and the slurry obtained in S3 are mixed together, and the temperature of the reactor is set to -10°C, 0°C, and 10°C in a closed high-pressure reactor for 30 min respectively. The atmosphere in the high-pressure reactor is saturated ammonia and 5 atmospheres of pressure.
[0039] S5: Take out the reaction product of step S4 and spray dry it. The spray dryer requires a nitrogen atmosphere and an oxygen content of less than 0.01 ppm. The drying temperature is 95°C to obtain Li2TaCl6-polydopamine-coated LZCFO electrolyte, which is recorded as LTC-PDA@LZCFO. Figure 1 shown.
[0040] S6: Mix LTC-PDA@LZCFO powder with binder GR-508 and starch. The mass ratio of electrolyte powder: binder: starch is 100:3:5. The solvent is a deionized water solution containing 15% NH4Cl. Prepare a slurry with a solid content of 25%. The slurry is dispersed from fast to slow at a rate of 2000r / min, 1000r / min, and 500r / min for 6 hours. After dispersion, it is transferred to a rotary evaporator for evaporation at 60°C to increase the solid content of the slurry to 50%. At the same time, the pH is reduced to 7±1. Then the slurry is taken out and coated on a polyimide base film with a thickness of 14μm using a coater. The coating thickness is 2μm. Both sides of the base film are coated. After coating, it is continuously dried at 200°C under negative pressure for 8 hours. Starch@LTC-PDA@LZCFO electrolyte membrane Figure 2 shown.
[0041] S7: Place the electrolyte membrane obtained in S6 into an ALD atomic deposition device, and plate a layer of 3 nm thick tungsten metal on one side. The side plated with tungsten metal is used as the negative electrode side of the electrolyte layer to obtain the electrolyte membrane of this scheme. Figure 3 As shown, (a) is the conceptual structure diagram of the electrolyte membrane; (b) is the SEM cross-sectional diagram of the electrolyte membrane after coating in step S6; and (c) is the interface phase diagram of the product composition after the all-solid-state battery cycle.
[0042] Embodiment 2: S1: LiCl, ZrCl4, LiF and Li2O are mixed in a molar ratio of 2:1:0:0, and the materials are mixed in a mixing machine for 30 minutes, maintaining an argon atmosphere with oxygen; then the mixed materials are put into a ball mill, the ball-to-material ratio is 40:5, the ball diameter is selected to be 10mm:5mm:3mm=3:1:1, and an atmosphere mixture of oxygen and argon is introduced into the ball mill, the atmosphere mixture includes 99% volume of argon and 1% volume of oxygen, and high-energy ball milling is performed, the speed is set at 500r / min, the ball milling time is 15min, and the ball mill is opened every 30min for gas renewal, and finally the powder in the ball mill is taken out for refinement to obtain LZC powder with a particle size of 2μm.
[0043] S2: LiCl, TaCl4, ScCl3, and NH4Cl were added to deionized water at a molar ratio of 2.3:0.7:0.3:3, stirred at a stirring rate of 300 r / min for 30 min, and then dried at 200 °C to a powder state to obtain Li 2.3 Ta 0.7 Sc 0.3 Cl6 electrolyte.
[0044] S3: Add Li to the LiCl saturated solution 2.3 Ta 0.7 Sc 0.3 Cl6 electrolyte, and then add a certain amount of polydopamine, the molar ratio of electrolyte to polydopamine is controlled at 1:0.1, fully stirred at 50°C, and the solution is continuously concentrated to control the viscosity to 300±20 cps.
[0045] S4: The powder obtained in S1 and the slurry obtained in S3 are mixed together, and the temperature of the reactor is set to -20°C, 0°C, 20°C, 40°C, and 60°C in a closed autoclave for 15 minutes respectively. The atmosphere in the autoclave is saturated ammonia and 5 atmospheres.
[0046] S5: Take out the reaction product of step S4 and spray dry it. The spray dryer requires a nitrogen atmosphere and an oxygen content of less than 0.01 ppm. The drying temperature is 100°C to obtain Li 2.3 Ta 0.7 Sc 0.3 Cl6-polydopamine coated LZCFO electrolyte, denoted as LTSC-PDA@LZCFO.
[0047] S6: Mix LTSC-PDA@LZCFO powder with a binder and a pore-forming agent. The binder is GR-508 produced by Gaorui Power Source, and the pore-forming agent is starch. The mass ratio of electrolyte powder: binder: starch is 100:3:15. The solvent is a deionized water solution containing 15% NH4Cl. A slurry with a solid content of 15%-30% is prepared. The slurry is dispersed from fast to slow at a rate of 150-3000r / min for 6h, and then transferred to a rotary evaporator for evaporation at 60°C to increase the solid content of the slurry to 50%. At the same time, the pH is reduced to 7±1. The slurry is then taken out and coated on a polyimide base film with a thickness of 7μm using a coater. The coating thickness is 3μm, and both sides of the base film are coated. After coating, it is continuously dried at a temperature of 200°C under negative pressure for 8h.
[0048] S7: Place the electrolyte membrane obtained in S6 into an ALD atomic deposition device, and coat a layer of metal element tungsten with a thickness of 1 nm on one side. The side coated with tungsten is used as the negative electrode side of the electrolyte layer to obtain the electrolyte membrane of this scheme.
[0049] Embodiment 3: S1: LiCl, ZrCl4, LiF and Li2O are mixed in a molar ratio of 1.5:1:0.5:0, and the materials are mixed in a mixing machine for 15 minutes, maintaining an argon atmosphere; then the mixed materials are put into a ball mill, the ball-to-material ratio is 40:4, the ball diameter is selected to be 10mm:5mm:3mm=2:2:3, argon is introduced into the ball mill, high-energy ball milling is performed, the speed is set at 600r / min, the ball mill time is 360min, and the ball mill is opened every 30min for gas renewal, and finally the powder in the ball mill is taken out for refinement to obtain a powder with a particle size of 1.2μm.
[0050] S2: LiCl, TaCl4, ScCl3, ErCl3, and NH4Cl were added to deionized water at a molar ratio of 3:0.33:0.33:0.33:3, stirred at a stirring rate of 150 r / min for 60 min, and then dried at 200 °C to a powder state to obtain Li 2.99 Ta 0.33 Sc 0.33 Er 0.33 Cl6 electrolyte.
[0051] S3: Add LiCl to the saturated solution to obtain Li 2.99 Ta 0.33 Sc 0.33 Er 0.33 Cl6 electrolyte, and then add a certain amount of polydopamine, the molar ratio of electrolyte to polydopamine is controlled at 1:0.5, fully stirred at 50°C, and the solution is continuously concentrated to control the viscosity at 500±20 cps.
[0052] S4: The powder obtained in S1 and the slurry obtained in S3 are mixed together, and the temperature of the reactor is set to 20° C., 40° C., 60° C., 80° C., 100° C., and 120° C. in a closed autoclave for 10 min respectively. The atmosphere in the autoclave is saturated ammonia gas and 5 atmospheres of pressure.
[0053] S5: Take out the reaction product of S4 and spray dry it. The spray dryer requires nitrogen atmosphere and oxygen content less than 0.01ppm. The drying temperature is 90℃ to obtain Li 2.99 Ta 0.33 Sc 0.33 Er 0.33 Cl6-polydopamine coated LZCFO electrolyte, denoted as LTSEC-PDA@LZCFO.
[0054] S6: LTSEC-PDA@LZCFO powder was mixed with binder Gr-506 and starch. The mass ratio of electrolyte powder: binder: starch was 100:5:1. A deionized water solution containing 15% NH4Cl was used as the solvent to prepare a slurry with a solid content of 20%. The slurry was dispersed at a rate of 3000 r / min for 6 hours. After dispersion, it was transferred to a rotary evaporator for evaporation at 60°C to increase the solid content of the slurry to 50%. At the same time, the pH was reduced to 7±1. The slurry was then taken out and coated on a polyimide base film with a thickness of 10 μm using a coater. The coating thickness was 2 μm and both sides of the base film were coated. After coating, it was continuously dried at 200°C under negative pressure for 8 hours.
[0055] S7: Place the electrolyte membrane obtained in S6 into an ALD atomic deposition device, and coat a layer of metal element tungsten with a thickness of 5 nm on one side. The side coated with tungsten is used as the negative electrode side of the electrolyte layer to obtain the electrolyte membrane of this scheme.
[0056] Comparative Example 1: Compared with Example 1, S3 is not included, and the powder obtained from S2 is directly mixed with the powder obtained from S1 and then enters S4.
[0057] Comparative Example 2: Compared with Example 1, no pore-forming agent starch was added in S6, and the binder and a 15% NH4Cl deionized water solution were directly prepared into a slurry.
[0058] Comparative Example 3: Compared with Example 1, no binder was added in S6, and starch and a 15% NH4Cl deionized water solution were directly prepared into a slurry.
[0059] Comparative Example 4: Compared with Example 2, S4 was kept at -20°C for 75 min, and the other conditions remained unchanged.
[0060] Comparative Example 5: Compared with Example 2, S5 does not use spray drying but uses freeze drying.
[0061] Comparative Example 6: Compared with Example 2, in S6, a rotary evaporator was not used for evaporation, but an ordinary evaporating dish was used for evaporation in a vacuum drying oven.
[0062] Comparative Example 7: Compared with Example 3, S7 is eliminated.
[0063] Comparative Example 8: Compared with Example 3, the deionized water containing 15% NH4Cl used in all steps was replaced with pure deionized water.
[0064] Comparative Example 9: Compared with Example 3, the saturated LiCl solution in S3 was replaced with pure deionized water.
[0065] Comparative Example 10: Compared with Example 3, S2, S3 and S4 are eliminated.
[0066] Comparative Example 11: Compared with Example 1, TaCl4 is not used in S2.
[0067] Comparative Example 12: Compared with Example 2, TaCl4 is not used in S2.
[0068] Comparative Example 13: Compared with Example 3, TaCl4 is not used in S2.
[0069] Test example: 1. EIS impedance comparison. The results are as follows Figure 4 As shown, compared with comparative examples 1 to 4, the EIS impedance of the electrolyte membranes of Example 1 and Example 2 is only 25% of that of the comparative examples, indicating that the present solution significantly improves the lithium ion conductivity.
[0070] 2. Cycle test: The electrolyte powder obtained in step S5 of Example 3 and Comparative Example 7 was mixed with the positive electrode active material NCM83 at a mass ratio of 3:7, and 0.05 mass ratio of VGCF was added. The positive electrode powder was obtained by grinding for 15 minutes. 20 mg of the positive electrode mixed powder was used, and the electrolyte membranes of Example 3 and Comparative Example 7 were respectively used. The negative electrode used a lithium metal sheet with a thickness of 20 μm. The batteries were assembled into all-solid-state batteries for testing and the results were as follows: Figure 5 As shown, compared with Comparative Example 7, the cycle performance of Example 3 has a very large advantage, and the capacity retention rate is still 100% after 50 cycles, while the capacity retention rate of Comparative Example 7 is only close to 95%.
[0071] III. Performance test: The electrolyte powder obtained in step S5 of Examples 1 to 3 and Comparative Examples 1 to 13 was respectively used and mixed with the positive electrode active material NCM83 at a mass ratio of 3:7, and 0.05 mass ratio of VGCF was added, and the positive electrode powder was obtained by grinding for 15 minutes. 20 mg of the positive electrode mixed powder was used, and the electrolyte membranes of each embodiment and each comparative example were respectively used, and the negative electrode used a lithium metal sheet with a thickness of 20 μm, and they were assembled into all-solid-state batteries for testing to obtain the results in Table 1:
[0072] As can be seen from the above table, compared with the comparative example, the three embodiments all show good coulombic efficiency and capacity retention rate, indicating that the present solution has very obvious improvements in improving ionic conductivity, interface stability and reducing side reactions. In the above embodiments, the description of each embodiment has its own emphasis. For the part that is not described or recorded in detail in a certain embodiment, please refer to the relevant description of other embodiments.
[0073] The embodiments described above are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, a person skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present application, and should all be included in the protection scope of the present application.
Claims
1. A method for preparing a solid electrolyte membrane, characterized in that: The following steps are involved: S1, mixing lithium chloride, a first halide, LiF, and Li2O, and ball-milling to obtain a first mixed powder; S2, adding lithium chloride, a second halide, and ammonium chloride to deionized water, stirring, and drying the solution to a powder state to obtain an electrolyte, wherein the second halide is a combination of one or more of YCl3, ScCl3, ErCl3, InCl3 and TaCl4; S3, adding the electrolyte obtained in S2 to a solution saturated with lithium chloride, and then adding polydopamine, stirring, and concentrating to control the viscosity at a set value to obtain a mixed slurry; S4, mixing the first mixed powder obtained in S1 with the mixed slurry obtained in S3, and reacting them at a set pressure and a set temperature to obtain an intermediate product; S5, drying the intermediate product to obtain Li 2+b Ta a X b Cl6-polydopamine-coated LZCFO electrolyte, denoted as LTXC-PDA@LZCFO; S6, mixing the LTXC-PDA@LZCFO with a binder and a pore-forming agent, adding a solvent to prepare a slurry, dispersing and evaporating to obtain an electrolyte slurry, coating the electrolyte slurry on both sides of the polyimide-based film, and drying to obtain an electrolyte membrane; S7. Performing atomic deposition on the electrolyte membrane to form a metal layer on one side to obtain the solid electrolyte membrane.
2. The preparation method according to claim 1, characterized in that: In step S1, the first halide is ZrCl4; the molar ratio of the lithium chloride, the first halide, LiF, and Li2O is d:e:f:g, wherein 0<d≤4, 0<e≤1, 0≤f≤2, 0≤g≤0.5; the particle size of the first mixed powder after refinement is 1μm-2μm.
3. The preparation method according to claim 1, characterized in that: In step S2, the molar ratio of lithium chloride, the second halide and ammonium chloride is x:y:z, wherein 0<x≤3, 0<y≤1.5, 0<z≤3; and the drying is to dry the solution to a powder state at 200-800°C.
4. The preparation method according to claim 1, characterized in that: The electrolyte in step S3 is Li 2+b Ta a X b Cl6, wherein X is 0, 1 or a combination of 2 or more of Y, Sc, Er and In, 0.1≤a≤3, 0≤b≤5; the molar ratio of the electrolyte to polydopamine is 1:(0.01-0.5), the stirring is carried out at 5-200°C, and the viscosity after concentration is set to 10-5000cps.
5. The preparation method according to claim 1, characterized in that: In step S4, the set temperature is -20°C to 150°C, the set pressure is 1-5 standard atmospheres, and the reaction is carried out in an atmosphere of saturated ammonia.
6. The preparation method according to claim 1, characterized in that: The drying conditions in step S5 are: in a spray dryer with a nitrogen atmosphere, the drying temperature is 60-300°C.
7. The preparation method according to claim 1, characterized in that: In step S6, the binder is a PMMA-based binder, the pore-forming agent is starch, the mass ratio of the electrolyte powder: binder: starch is 100: (1-5): (1-15), and the solvent is a deionized water solution containing 15% NH4Cl.
8. The preparation method according to claim 1, characterized in that: The dispersion in step S6 is to disperse the slurry from fast to slow at a rate of 150-3000r / min for 2h-50h; the evaporation is to evaporate at 60-120°C in a rotary evaporator to increase the solid content of the slurry to 45%-55%, and at the same time reduce the pH to 7±1; the thickness of the polyimide-based membrane is 3-14μm, the porosity is ≥50%, and the coating thickness is 1μm-5μm.
9. The preparation method according to claim 1, characterized in that: The metal layer in step S7 is a combination of one or more of the metal element tungsten, tungsten oxide, and tungsten carbide.
10. Use of a solid electrolyte membrane obtained by the method for preparing a solid electrolyte membrane according to any one of claims 1 to 9 in a battery.
Citation Information
Patent Citations
Preparation method and application of bifunctional solid electrolyte for solid-state battery
CN112768749A
Zirconium-based composite solid electrolyte powder for all-solid-state lithium ion battery and preparation method of zirconium-based composite solid electrolyte powder
CN118589030A
Oxidation halide solid electrolyte composite material, preparation method thereof and battery
CN119400937A
PROTECTION OF SOLID ELECTROLYTES
FR3111475A1
Solid electrolyte composition, method of forming the same, and method of forming all-solid-state batteries using the same
KR1020180043152A